IMPLEMENTASI PENDIDIKAN AKHLAK DALAM PEMBENTUKAN KARAKTER ISLAMI SISWA KELAS VIII DI MTS MUHAMMADIYYAH 01 MEDAN - Wira Buana Satria Daulay; Zaimah Zahirah Lubis; Dilla Ayu Purnama; Zainal Abidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of moral education in developing the Islamic character of eighth-grade students at Madrasah Tsanawiyah (MTs) Muhammadiyah 01 Medan, as well as to identify the supporting and hindering factors in its execution. This study employs a qualitative approach with a phenomenological design. The data collection process was conducted through observation, in-depth interviews, and document analysis. Field findings indicate that moral education at the madrasah is implemented comprehensively, integrated through classroom learning activities, habituation of worship such as congregational Duha prayer, the application of an Islamic school culture, and teacher role modeling. The success of this implementation is supported by a religious madrasah climate, teachers who consistently provide exemplary behavior, and support from parents. On the other hand, the main challenges hindering the process include the strong influence of social media and the lack of supervision from some parents at home. Broadly speaking, this study concludes that the consistent and integrated implementation of moral education is proven effective in shaping students' Islamic character gradually and sustainably.